KETERANGAN ANAK SEBAGAI SAKSI KORBAN TINDAK PIDANA PENCABULAN DALAM UNDANG-UNDANG TINDAK PIDANA KEKERASAN SEKSUAL - Kevin Febriansyah (2022)
Insufficient preliminary evidence is an obstacle in the problem of sexual violence that is often faced. Sufficient preliminary evidence is needed to suspect a criminal act and suspect the suspect. At least two pieces of evidence are required among the legal evidence as stated in Article 184 paragraph (1) of the Criminal Procedure Code. However, the required minimum of two pieces of evidence proof system. The purpose of this paper is to analyze the problems of evidence in the testimony of children as victims in the Act on the Crime of Sexual Violence and to analyze related solutions in overcoming sexual violence against minors. This research method uses a normative juridical approach and uses primary legal materials in the form of Law Number 12 of 2022 concerning the Crime of Sexual Violence and related regulations. The results showed that the testimony of the victim's witness must be accompanied by at least one other piece of evidence, for example visum et repertum, in this case the witness (victim) is sufficient to determine the perpetrator as a suspect. Therefore, it can be understood that the testimony of a child victim of sexual abuse should have been able to form a judge's conviction to decide a criminal act for the actions taken by the defendant to the victim. Regarding solutions for dealing with criminal acts of sexual violence, efforts are made through preventive efforts, repressive efforts, and the last effort, namely Penal efforts.